An analysis of the mechanism of the influence of college students’ involutional behaviour on subjective well-being - Zhu, Qin; Lu, Chengyan; Huang, Zhitian (Transactions on Social Science, Education and Humanities Research, 2024)
Youth prosperity is the prosperity of the country, youth strength is the strength of the country, in the face of the current severe employment situation and strong economic downward pressure, in order to seek development, college students are forced to fall into the ranks of the involution, however, the ensuing health problems, psychological problems, are letting us reflect on the correctness of the involution, and whether it will cause a significant negative impact on the subjective sense of well-being of the college students, and how should we distinguish and measure the involution. Based on the research hypothesis that introspection is a kind of meaningless mental internal consumption, this paper analyses the samples by questionnaire survey, by grouping the samples of college students’ participation in cet4/6 and competitions to conclude that college students’ degree of introspection has a significant negative impact on their subjective well-being, and that the participation in cet4/6 and competitions can serve as a grouping variable of the degree of introspection, and furthermore, the mediating effect between the two is analysed by the individual effect test. In addition, the mediating effect between the two was analysed through the individual effect test, and through the interpretation of the social atmosphere and personal pursuit, it was concluded that there is indeed the existence of individuals who are happier the more introspective they are, and finally, corresponding suggestions were put forward for the current social situation.